2019
DOI: 10.1136/bcr-2018-226337
|View full text |Cite
|
Sign up to set email alerts
|

DisseminatedSalmonellainfection

Abstract: A 47-year-old Malay man who presented with fever, poor oral intake and loss of weight for 1 month duration. Further work-up revealed evidence of disseminated Salmonella infection that was further complicated with pericardial and pleural empyema. Cultures from pericardial and pleural fluids grew Salmonella species with negative serial blood cultures. Contrast enhanced CT thorax showed pleural effusion with large pericardial effusion. The patient was treated with antibiotics and drainage of pericardial and pleur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The strain is a common food contaminant, and has been incriminated in several outbreaks in Malaysia in recent years [ 11 ]. Moreover, human infections are being repeatedly reported, with chicken and chicken products being one of the most common sources of infection [ 11 , 27 , 28 ]. Therefore, it has become paramount to investigate and understand the potential role of chicken (meat and meat products) in the dissemination of Salmonella species.…”
Section: Discussionmentioning
confidence: 99%
“…The strain is a common food contaminant, and has been incriminated in several outbreaks in Malaysia in recent years [ 11 ]. Moreover, human infections are being repeatedly reported, with chicken and chicken products being one of the most common sources of infection [ 11 , 27 , 28 ]. Therefore, it has become paramount to investigate and understand the potential role of chicken (meat and meat products) in the dissemination of Salmonella species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the human gut microbiota is affected by a wide range of host factors such as diet, genetics, disease, region, and medical conditions (He et al, 2018;Wan et al, 2019). Envfit (see Methods) was conducted to quantitatively evaluate the effect of individual infant factors on the gut microbiota.…”
Section: Multi-factorial Impacts and Disorganized Development Of Gut ...mentioning
confidence: 99%
“…Clinical studies have demonstrated distinct compositions of gut microbiota in subjects with obesity ( Ley et al., 2006 ), diabetes ( Qin et al., 2012 ), cystic fibrosis ( Hayden et al., 2020 ), kidney disease ( Joossens et al., 2019 ), SAM ( Subramanian et al., 2014 ), and moderate acute malnutrition (MAM) ( Raman et al., 2019 ) compared to the compositions of healthy individuals. In clinical practice, individual somatic conditions caused by microorganisms are relatively common such as Salmonella infection ( Johari et al., 2019 ) and rabies ( Hemachudha et al., 2013 ). In regard to the growth of children, a previous study revealed the development of the gut microbiota from infancy to childhood is spontaneous ( Stewart et al., 2018 ) and synchronizes with the maturation of both the somatic body and nervous system.…”
Section: Introductionmentioning
confidence: 99%